Customer satisfaction as a mediator variable between service quality and customer loyalty for a bank in Indonesia - Syamsul Bahri; Ritha Fatimah Dalimunthe; Paham Ginting; Rismayani; Beby Karina Fawzeea Sembiring (Expert journal of marketing, 2017)
This study aims to analyze the effect of service quality toward satisfaction and customer loyalty for PT. BNI (Persero) Tbk, Aceh Province. The article also analyses customer satisfaction as a mediator variable between service quality and customer loyalty. The sampling technique in the study was based on cluster and convenience sampling with corresponding criteria; each respondent has a bank account and saving for at least one year. The primary data were collected from respondents using the structured questionnaires. A total of 220 questionnaires were distributed in five branch offices of PT. BNI (Persero) Tbk operating in Aceh Province, namely the branchs of Lhokseumawe, Bireuen, Langsa, Sigli and Meulaboh. The results showed that service quality has a significant and positive effect toward satisfaction and customer loyalty for PT. BNI (Persero) Tbk Aceh Province. Meanwhile, the variable of customer satisfaction can mediate the effect of service quality toward customer loyalty. However, the study found that service quality is the important element in increasing satisfaction and customer loyalty in national banking.
2758454-9; 2344-6773; Expert journal of marketing; 778946770